Augmented Reality in STEM Education: Trends and Insights from 2012 to 2021 - Prelia Dwi Amanah; Rahmatullah Rahmatullah; Gunawan Gunawan (Indonesian Journal of STEM Education, 2022)
This study aims to analyze trends and developments in research on augmented reality (AR) in Science, Technology, Engineering, and Mathematics (STEM) education during the 2012–2021 period through a descriptive bibliometric analysis approach. Data were obtained from the Dimensions.ai and Publish or Perish (PoP) database using the keyword combination "augmented reality" and "STEM education," yielding 127,096 publications analyzed using VOSviewer software for keyword network visualization, density mapping, and temporal overlay. Results indicate significant publication growth, peaking in 2020 (18,717 publications) and 2021 (18,223 publications), reflecting the academic response to post-pandemic digital acceleration. Book chapters dominate publication types (41.35%), while Lecture Notes in Computer Science constitutes the most prolific source. SDG analysis reveals the dominance of SDG 4: Quality Education (7,232 publications). Keyword cluster mapping identifies four dominant research themes: clinical applications, technology intervention design, empirical testing, and learner-centered formal education, with student, intervention, and science as the most central thematic nodes. These findings confirm that AR research in STEM education has shifted from a technical orientation toward pedagogical integration centered on student learning impact.